Analysis of Humor Making Techniques in the WIT Comedy Program (Waktu Indonesia Timur) - Ratri Harida (Peneliti.net, 2018)
Verbal humor tends toexploit the linguistics aspects such as word, phrase, and sentences as the triggers of laugh. According to Berger there are eleven verbal humor techniques: bombast, infantilism, irony, misunderstanding, pun, repartee, ridicule, sarcasm, satire, sexual allusion, and outwitting. The aims of this research were to understand and to analyze humor as a part of linguistic phenomena. This research is descriptive qualitative research. The subject of the research was the record of WIT program. The data were collected through documentation technique. There was only one Berger’ humor technique which was not used in WIT; sexual allusion technique. Bombast and outwitting techniques were used more, while infantilism, irony, and pun were less used in WITcomedy program